THE ROLE OF VASCULAR GROWTH FACTORS IN THE PATHOGENESIS OF PLACENTAL INSUFFICIENCY - E. V. Volkova; Yu. V. Kopylova (Акушерство, гинекология и репродукция, 2016)
Presently, the placental insufficiency still remains an important issue not only in obstetrics, perinatology and pediatrics, but also it has impact on public health in general being one of the major causes of perinatal morbidity and mortality. The outcome of placental  insufficiency for the fetus is the fetal growth retardation syndrome, intrauterinehypoxia or death. This article presents modern concepts of the etiology, pathogenesis and morphogenesis of placental insufficiency including the latest information about the role of vascular growth factors and their receptors in the regulation of placental angiogenesis and their effect on formation of the placenta.